Transcranial Doppler imaging ultrasound assessment of cerebral blood flow velocity and abnormalities in steady-state sickle cell anaemia children, Southwest Nigeria: - Oderanti, Oyetoke C.; Oninla, Samuel O.; Akintola, Moshood A.; Abayomi, Olawale A.; Olagunju, Funso A.; Adesokan, Funmilola J. (International Journal of Contemporary Pediatrics, 2025)
Background: Monitoring cerebral blood flow velocity in children with sickle cell anaemia is valuable and advocated and early detection of abnormal velocity affords appropriate management. This study assessed the blood flow velocities in the large intracranial arteries of the participants and determined abnormalities (risks for stroke). Methods: The blood flow velocity in the middle and anterior cerebral arteries of the study participants (2–14 years) was assessed using a transcranial doppler (TCD) imaging ultrasound machine. The risk of stroke for each patient was determined by the greatest time-average mean maximum velocity (TAMMV) in centimeters/second (cm/s) in any of the insonated arteries. And using the Stroke Prevention Trial (STOP) criteria, the subjects were classified into having standard, conditional or high risk for stroke. Results: Out of the 110 participants, males were 61 (55.5%) and females 49 (44.5%). The overall mean TAMMV was 135.50±28.62 cm/s and the 2‒5-year-old group presented the highest mean TAMMV (141.31±29.97). The overall mean TAMMVs for the middle and anterior cerebral arteries were 151.95±39.29 cm/s and 117.38±39.85 cm/s, respectively (t=8.583, p<0.001). According to the STOP criteria, fifty-four (49.1%), 40 (36.4%) and 16 (14.5%) of the subjects had standard, conditional and high risk for stroke, respectively. A comparison of the pattern of risk for stroke identified by Stop criteria (non-imaging) and the adjusted Stop criteria (imaging) revealed a statistically significant difference (p<0.001). Conclusions: The prevalence (50.9%) of abnormal velocity (Stop criteria) in this study was high and therefore, regular measurement of the TAMMV in SCA patients is recommended.